2012
DOI: 10.1155/2012/239638
|View full text |Cite
|
Sign up to set email alerts
|

JCM-16021, a Chinese Herbal Formula, Attenuated Visceral Hyperalgesia in TNBS-Induced Postinflammatory Irritable Bowel Syndrome through Reducing Colonic EC Cell Hyperplasia and Serotonin Availability in Rats

Abstract: The present study aimed to investigate the analgesic effect of JCM-16021, a revised traditional Chinese herbal formula, on postinflammatory irritable bowel syndrome (PI-IBS) in rats. The trinitrobenzene sulfonic (TNBS) acid-induced PI-IBS model rats were orally administrated with different doses of JCM-16021 (1.2, 2.4, and 4.8 g/kg/d) for 14 consecutive days. The results showed that JCM-16021 treatment dose-dependently attenuated visceral hyperalgesia in PI-IBS rats. Further, the colonic enterochromaffin (EC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…This results in acute inflammation in the mucosa and submucosa of the treated colon and can be characterized by edema, hemorrhage, infiltration of immune cells and occasionally ulceration. In this chemical-induced model, typically, visceral hypersensitivity was developed in the absence of mucosal damage [ 72 ].…”
Section: Preclinical Experimental Models Of Ibsmentioning
confidence: 99%
“…This results in acute inflammation in the mucosa and submucosa of the treated colon and can be characterized by edema, hemorrhage, infiltration of immune cells and occasionally ulceration. In this chemical-induced model, typically, visceral hypersensitivity was developed in the absence of mucosal damage [ 72 ].…”
Section: Preclinical Experimental Models Of Ibsmentioning
confidence: 99%
“…Based on the holistic review and syndrome differentiation in Traditional Chinese Medicine (TCM) acupoints with different functions should be selected according to the different diseases and syndromes, and then the curative effect is remarkable [16, 17]. In classical acupuncture, acupoints with effects of tranquilizing the mind, relieving pain, and regulating the functions of stomach and intestines all showed satisfied effect on IBS [18].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying EC cell hyperplasia in PI-IBS have yet to be fully elucidated, but they were considered to be associated with CD4 + T lymphocytes, particularly the Th1/Th2 ratio. It was reported that TNF- α can downregulate CD4 + T-cell response and IL-6 initiates maturation of Th2 cells from Th0; thus, the Th1/Th2 ratio maybe affected by these cytokines [ 21 ]. Our previous study demonstrated that SGD treatment could decrease the levels of TNF- α , IL-1 β , IL-6, and IL-18 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PI-IBS animal models were induced as previously described [ 20 , 21 ]. Briefly, the animals were fasted overnight with free access to water, and a mixture solution of TNBS with 50% ethanol (0.8 mL per rat) was administered into the colon by a plastic catheter.…”
Section: Methodsmentioning
confidence: 99%